Analysis of Parking Needs and System in Bengkayang Central Market - Arfando, Gio; Azwansyah, Heri; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2025)
Bengkayang Regency, located in West Kalimantan Province, plays a strategic role as an economic and trade centre in the border region. One of its busiest areas is the Bengkayang Central Market, a hub for the distribution of goods and services. The high intensity of trading activities has led to increased parking demand, which, if left unmanaged, can result in congestion, reduced comfort, and disruptions to traffic flow. This study aims to identify parking characteristics, determine parking space requirements, and propose alternative arrangements for the Bengkayang Central Market. Primary data were collected through direct observations of parking inventory and vehicle entry"“exit recording, while secondary data included market layout plans. Analysis covered accumulation, volume, duration, capacity, turnover rate, and parking index. Findings show that the parking capacity for two-wheeled vehicles is 145 PSU, with a demand of 25 PSU, while four-wheeled vehicles have a capacity of 14 PSU and a demand of 4 PSU. The study recommends applying 0 ° angle markings for four-wheeled vehicles and 90 ° angle markings for two-wheeled vehicles to enhance space efficiency and reduce traffic disruption around the market area.